Intersectionality and the arts: counterpublic memory-making in postconflict Peru - Falcón, Sylvanna M. (International journal of transitional justice, 2018)
Producing memories through the creation of art has been one of many outcomes of the transnational justice period in Peru by both state and nonstate social actors. Art projects that are independent from state-led transitional justice initiatives convey a perspective about the internal conflict and the state’s legacies of marginalization that is in tension with a dominant discourse that seeks to absolve the state and urban elites of culpability. This article examines three public art projects that are conducive to applying an intersectionality feminist analysis to consider how widespread structural and systemic violence is rooted in a lengthy history of societal exclusions based on a combination of gender, race/ethnicity and socioeconomic class.